Early versus delayed complex abdominal wall reconstruction with biologic mesh following damage-control surgery. Issue 3 (4th March 2021) - Gogna, Shekhar; Latifi, Rifat; Choi, James; Con, Jorge; Prabhakaran, Kartik; Anderson, Patrice L.; Policastro, Anthony J.; Klein, Joshua; Samson, David J.; Smiley, Abbas; Rhee, Peter
Abstract : BACKGROUND: Damage-control surgery for trauma and intra-abdominal catastrophe is associated with a high rate of morbidities and postoperative complications. This study aimed to compare the outcomes of patients undergoing early complex abdominal wall reconstruction (e-CAWR) in acute settings versus those undergoing delayed complex abdominal wall reconstruction (d-CAWR). METHOD: This study was a pooled analysis derived from the retrospective and prospective database between the years 2013 and 2019. The outcomes were compared for differences in demographics, presentation, intraoperative variables, Ventral Hernia Working Grade (VHWG), US Centers for Disease Control and Prevention wound class, American Society of Anesthesiologists (ASA) scores, postoperative complications, hospital length of stay, and readmission rates. We performed Student's t test, χ 2 test, and Fisher's exact test to compare variables of interest. Multivariable linear regression model was built to evaluate the association of hospital length of stay and all other variables including the timing of complex abdominal wall reconstruction (CAWR). A p value of <0.05 was considered significant. RESULTS: Of the 236 patients who underwent CAWR with biological mesh, 79 (33.5%) had e-CAWR. There were 45 males (57%) and 34 females (43%) in the e-CAWR group. The ASA scores of IV and V, and VHWG grades III and IV were significantly more frequent in the e-CAWR group compared with the d-CAWR one. Postoperatively, the incidence of surgical site occurrence, Clavien-Dindo complications, comprehensive complication index, unplanned reoperations, and mortality were similar between the two groups. Backward linear regression model showed that the timing of CAWR ( β = −11.29, p < 0.0001), ASA ( β = 3.98, p = 0.006), VHWG classification ( β = 3.62, p = 0.015), drug abuse ( β = 13.47, p = 0.009), and two comorbidities of cirrhosis ( β = 12.34, p = 0.001) and malignancy ( β = 7.91, p = 0.008) were the significant predictors of the hospital length of stay left in the model. CONCLUSION: Early CAWR led to shorter hospital length of stay compared with d-CAWR in multivariable regression model. LEVEL OF EVIDENCE: Therapeutic, level IV.